Pengaruh Kualitas Sistem Informasi, Kualitas Informasi, Dan Perceived Usefulness Pada Kepuasan Pengguna Sistem Informasi Akuntansi - Mangun Buana, Ida Bagus Gede Mawang; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi; Vol 22 No 1 (2018), 2018)
PDAM Tirta Mangutama is one of the regional companies that have integrated accounting information system in managing employees' performance in providing accurate accounting information. Large working area of course must be balanced with good performance. The purpose of this study is to determine the effect of quality information systems, information quality, and perceived usefulness on user satisfaction accounting information system. This research is causal explanatory relationship. The research was conducted at PDAM, located at Jalan Bedahulu No 3 Denpasar. The result of research is Quality accounting information system, information quality and perceived usefullness have positive and significant influence on user satisfaction of Accounting Information System. Coefficient of determination (R2) of 0.554 this means 55.4 percent of user satisfaction Accounting Information on PDAM Tirta Mangutama Badung regency influenced by variable of Quality Accounting Information System, Information Quality, and Perceived Usefulness, on the contrary 44,6 percent influenced by variables others not examined. Keywords: Quality of Information Systems, Quality of Information, Perceived Usefulness of User Accounting Information System Satisfaction.